Ekspresi Emosi Tokoh Utama dalam Novel Laut Bercerita Karya Leila S. Chudori: Kajian Psikologi Sastra - Dian Safitri; Hidayatun Nur (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2026)
This study aims to describe the emotional expressions of the main character in the novel Laut Bercerita by Leila S. Chudori using a literary psychology approach. This research uses a qualitative descriptive method with content analysis techniques. The data source is the novel Laut Bercerita, while the data are in the form of text excerpts that reflect the emotional expressions of the main character, Biru Laut. The analysis is based on David Krech’s theory of emotional classification, which includes basic emotions, sensory-related emotions, and self-evaluative emotions. The results show that the main character experiences various emotional expressions such as happiness, sadness, fear, and anger, which are influenced by internal factors and external pressures, particularly political oppression and traumatic experiences. These emotions are expressed through narrative, dialogue, and actions, reflecting the complex psychological condition of the character. This study highlights that literary works serve as a medium to represent human psychological dynamics in a socio-political context.